IL‐1α and inflammasome‐independent IL‐1β promote neutrophil infiltration following alum vaccination. (4th November 2015) - Oleszycka, Ewa; Moran, Hannah B.T.; Tynan, Graham A.; Hearnden, Claire H.; Coutts, Graham; Campbell, Matthew; Allan, Stuart M.; Scott, Christopher J.; Lavelle, Ed C.
Abstract : Despite its long record of successful use in human vaccines, the mechanisms underlying the immunomodulatory effects of alum are not fully understood. Alum is a potent inducer of interleukin‐1 (IL‐1) secretion in vitro in dendritic cells and macrophages via Nucleotide‐binding domain and leucine‐rich repeat‐containing (NLR) family, pyrin domain‐containing 3 (NLRP3) inflammasome activation. However, the contribution of IL‐1 to alum‐induced innate and adaptive immune responses is controversial and the role of IL‐1α following alum injection has not been addressed. This study shows that IL‐1 is dispensable for alum‐induced antibody and CD8 T cell responses to ovalbumin. However, IL‐1 is essential for neutrophil infiltration into the injection site, while recruitment of inflammatory monocytes and eosinophils is IL‐1 independent. Both IL‐1α and IL‐1β are released at the site of injection and contribute to the neutrophil response. Surprisingly, these effects are NLRP3‐inflammasome independent as is the infiltration of other cell populations. However, while NLRP3 and caspase 1 were dispensable, alum‐induced IL‐1β at the injection site was dependent on the cysteine protease cathepsin S. Overall, these data demonstrate a previously unreported role for cathepsin S in IL‐1β secretion, show that inflammasome formation is dispensable for alum‐induced innate immunity and reveal that IL‐1α and IL‐1β are both necessary for alum‐induced neutrophil influx in vivo . Abstract : Alum is the most commonly used vaccine adjuvant, but the mechanism underlying its immunomodulatory effect is not fully understood. Lavelle and colleagues found that alum injection triggered the release of the cytokines IL‐1α and IL‐1β. Both cytokines controlled neutrophil influx into the site of vaccination but were not required for inflammatory monocyte or eosinophil recruitment. The alum‐induced IL‐1β release was independent of caspase 1 and inflammasome formation, but partly dependent on cathepsin S. This study highlights an intriguing role for cathepsin S in IL‐1β secretion, and reveals the importance of IL‐1α and IL‐1β cytokines in alum‐induced neutrophil influx.